Distinct effects of transition metal (cobalt, manganese and nickel) ion substitutions on the abiotic oxidation of pyrite: In view of hydroxyl radical production. (15th March 2022) - Lin, Xiaoju; Xia, Yulin; Wei, Gaoling; Zhou, Jingwen; Liang, Xiaoliang; Xian, Haiyang; Zhu, Jianxi; He, Hongping
Abstract: The abiotic oxidation of pyrite (FeS2 ) is a geochemically crucial reaction involved in acid mine drainage, the release of toxic trace elements and the generation of hydroxyl radicals ( OH) that can oxidize environmental substances. Studies on OH generation from the abiotic oxidation of pyrite have drawn wide interest, but the effects of the common substitution of transition metal ions on OH generation are still largely unknown, and worthy of comprehensive comparison. We therefore synthesized and comprehensively characterized micron-sized pyrites containing low concentrations of cobalt (Co), nickel (Ni), or manganese (Mn) ions, and tested the relative ability of these transition metal ion-substituted pyrites to generate OH under abiotic oxidation. We found that transition metal ion substitutions inhibited the growth of pyrite crystals to various extents and increased Fe–S bond distances, leading to distinct alterations in surface chemical composition, conductivity, and the exposure of active faces. These differences resulted in an increase in OH generation by the oxidation of transition metal ion-substituted pyrites, relative to pure pyrite, with the order of increase being Mn 2+ -substituted < Ni 2+ -substituted < Co 2+ -substituted pyrites. These substituent-dependent differences were explored by linking the crystal properties and physical chemistry of these pyrites to various reaction pathways that were possible in such contexts. For pure pyrite, the heterogeneous Fenton reaction was the chief generator of OH. The substitution of pyrite with Co 2+, which was redox-active, increased the conductivity of pyrite and accelerated the reduction of surface Fe 3+ to Fe 2+, resulting in a significant increase in H2 O2 and OH production. The substitution of pyrite with Mn 2+, which was also redox-active, likewise increased the conductivity; however, the high oxidizing ability of surface Mn 4+ inhibited the reduction of Fe 3+ and thus decreased OH generation. By contrast, the substitution of pyrite with Ni 2+ did not affect electron transfer but led to absolute exposure of the (111) face of pyrite, which increased its activity toward O2 and H2 O, slightly increasing H2 O2 and OH generation. These results highlight the vital role of transition metal ion-substituted pyrite in various geochemical processes.